Kepemimpinan Perempuan dalam Meningkatkan Kinerga Organisasi pada KOPRI (Korps PMII Putri) Wilayah Lampung - Siti Wuriyan (Mau'idhoh Hasanah, 2019)
ABSTRACT Leadership is the power of leaders to invite, influence, and move others to do something, in order to achieve effective and efficient goals in an organization. KOPRI is short for Putri PMII Corps, which is part of the PMII organization which is semi-autonomous, with the meaning "semi" there is a line of instructions, consultation and coordination. The meaning of "autonomous" is that KOPRI has the duties and authority in accordance with their fields in accordance with household regulations, and in charge of empowering both members and cadres of PMII women. In this study the authors specialize in the management of the KOPRI Lampung Region which addresses at Jalan Pahlawan Gang Cempaka, Number 40 Kedaton District, Bandarlampung City. Women's leadership in improving organizational performance in KOPRI Lampung Region, the authors can conclude. The type of leadership used by the KOPRI Lampung Region is the type of democratic leadership, it can be seen that each will plan or determine decisions or policies always prioritize deliberation, and does not rule out arguments from members into decisions agreed upon by the organization. The implementation of activities in KOPRI generally provides significant benefits for members even if they are not going well. Members can increase their capabilities with women's activities.